2022
DOI: 10.3389/fnut.2022.863029
|View full text |Cite|
|
Sign up to set email alerts
|

Consumption of Food Components of the Mediterranean Diet Decreases the Risk of Breast Cancer in the Makkah Region, Saudi Arabia: A Case-Control Study

Abstract: BackgroundBreast cancer is one of the leading causes of death worldwide, it affects both men and women. In Saudi Arabia, breast cancer has been the most prevalent type of cancer in women, for the past few years. Dietary habits and cultural beliefs vary according to region, and further studies are required to demonstrate the relationship between these dietary habits and cultural beliefs and the risk of developing breast cancer. This study is aimed to discover the relationship between preventive dietary factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…In Saudi Arabia, a case-control study by Azzeh et al found that adopting a dietary plan based on nutrient-rich foods, with weekly consumption of 1–2 servings of legumes and 1–5 servings of fish, daily intake of 3–5 servings of vegetables and fruits, 1–5 dairy product portions and over one cup of coffee or black tea reduced the risk of BC significantly ( p < 0.05) [ 35 ].…”
Section: Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia, a case-control study by Azzeh et al found that adopting a dietary plan based on nutrient-rich foods, with weekly consumption of 1–2 servings of legumes and 1–5 servings of fish, daily intake of 3–5 servings of vegetables and fruits, 1–5 dairy product portions and over one cup of coffee or black tea reduced the risk of BC significantly ( p < 0.05) [ 35 ].…”
Section: Dietary Patternsmentioning
confidence: 99%
“…The Mediterranean DP is a rich source of many nutrients that have been showed to decrease the risk of BC. Vitamin C helps strengthen immunity, Vitamin E, and Carotenoids exert chemo-preventive effects and omega 3 fatty acids reduce BC cell production by restraining the epidermal growth factor receptor [ 35 ]. Vitamin D, B Vitamins, phytochemicals, and essential minerals like calcium, magnesium and zinc also help to decrease the risk of BC.…”
Section: Dietary Patternsmentioning
confidence: 99%
“…Breast cancer appears to be one of the cancer types where fish consumption appears to have a favorable impact [179]. According to a study done in the Makkah area of Saudi Arabia, those who eat a Mediterranean-style diet can reduce their risk of breast cancer by 78.9% to 92.8% by eating up to five servings of fish and shellfish per week [180]. However, Engeset et al [181] found no proof that a person's overall fish consumption and risk of breast cancer were inversely related.…”
Section: Fishmentioning
confidence: 99%
“…Azzeh et al (2022) found that consuming 3-5 portions of animal products weekly, drinking more than 3 cups per day of tea, 3-5 servings per week of sh and seafood, more than 3 cups of coffee per week, ve portions of legumes or more every week, and consuming more than 3-5 servings of fruits and vegetables per week signi cantly reduced the likelihood of breast cancer. 39 However, the study only involved post-menopausal women, limiting the generalizability of the ndings to other populations. Salarabadi, Bidgoli, and Madani (2015) found that increased use of animal oils and reduced consumption of sh oil, milk, yogurt, white meat, soy, and nuts increased the likelihood of breast malignancy, whereas a diet composed of lettuce, cabbage, and carrots reduced the risk.…”
Section: Diet and Cancer In The Middle Eastmentioning
confidence: 99%
“…The majority of these studies were from Iran (n = 20), 6, 12-30 followed by Jordan (n = 3), [31][32][33] with Egypt, Saudi Arabia, Turkey, and Lebanon each having two studies. [34][35][36][37][38][39][40][41] Morocco, Syria, Yemen, Tunisia, and Qatar each had one study. [42][43][44][45][46] Fig.…”
Section: Included Papersmentioning
confidence: 99%